2019
DOI: 10.1111/ecog.04757
|View full text |Cite
|
Sign up to set email alerts
|

No biotic homogenisation across decades but consistent effects of landscape position and pH on macrophyte communities in boreal lakes

Abstract: It has been predicted that spatial beta diversity shows a decreasing trend in the Anthropocene due to increasing human impact, causing biotic homogenisation. We aimed to discover if vascular aquatic macrophyte communities show different spatial patterns in beta diversity in relation to land use and environmental characteristics in different decades from 1940s to 2010s. We aimed to discover if spatial structures differ between species-, phylogeny-and functional-based beta diversity. We used presenceabsence data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 71 publications
(180 reference statements)
3
46
1
Order By: Relevance
“…Therefore, sets of lakes should be understood as being connected in unique waterscapes, making the understanding of metacommunity organization context dependent and highly challenging. Recent findings in macrosystems ecology (Fergus et al ., 2018; Soranno et al ., 2019) and metacommunity ecology (García‐Girón et al ., 2020; Lindholm et al ., 2020) have increased knowledge on the spatial and temporal variability of physical, chemical, and biological features of lakes, which has further consequences for understanding a set of lakes as a meta‐ecosystem.…”
Section: Lakes As Waterscapes Underlying the Movement Of Organisms Anmentioning
confidence: 99%
“…Therefore, sets of lakes should be understood as being connected in unique waterscapes, making the understanding of metacommunity organization context dependent and highly challenging. Recent findings in macrosystems ecology (Fergus et al ., 2018; Soranno et al ., 2019) and metacommunity ecology (García‐Girón et al ., 2020; Lindholm et al ., 2020) have increased knowledge on the spatial and temporal variability of physical, chemical, and biological features of lakes, which has further consequences for understanding a set of lakes as a meta‐ecosystem.…”
Section: Lakes As Waterscapes Underlying the Movement Of Organisms Anmentioning
confidence: 99%
“…However, environmental changes can also determine the temporal turnover due to species sorting, potentially reaching rates higher than those predicted by stochastic dynamics (Dornelas et al, 2014). At the metacommunity level, long-term studies have shown either stable (e.g., Azeria and Kolasa, 2008;Huttunen et al, 2018;Lindholm et al, 2020) or changing metacommunities through time, due to environmental fluctuations or disturbances observed (e.g., Datry et al, 2016;Sarremejane et al, 2017;Cañedo-Argüelles et al, 2020). Nevertheless, the spatio-temporal scale of observation in each study could explain these differences, depending on whether or not the study duration covered those relevant environmental fluctuations (Korhonen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, naturally more eutrophic lakes are located at lower elevations and are mainly surrounded by agricultural land or settlements, while smaller and more oligotrophic lakes at higher elevations in the landscape are less affected by human activity and are surrounded by coniferous forest and peatlands. Key characteristics of these lakes are described in Table 2, and more information of the study area can be found in Lindholm et al (2019).…”
Section: Study Areamentioning
confidence: 99%
“…To represent functional diversity of aquatic macrophytes, we used four functional traits: growth form, perennation, common method of propagation and potential size (Supplementary material Appendix 2; Lindholm et al 2019). Growth form division consists of the following classes: ceratophyllid, elodeid, helophyte (incl.…”
Section: Species and Trait Datamentioning
confidence: 99%
See 1 more Smart Citation